(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
This article attempts to outline taboos in Ukrainian culture. The main outlook is given to the prohibition arising from Ukrainian value-significant conceptual images, in particular the bans related to the “death” concept. This paper focuses on analyzing Ukrainian idioms stock and literary works of Ukrainian writers, and distinguishing the main ways of taboos representation. The death image is one of the central Ukrainian archetypes. Ukrainians imagine death as an ambivalent nature symbol. On the one hand, it represents the end of the human’s body life, and on the other it is a kind of transition from this world to another world (eg. Ukrainians believed that after dying a person either falls asleep or becomes the guardian of the family). Everything associated with the loss of life and funeral processions requires special attention, since these ritual activities have a number of prohibitions and restrictions; also certain taboos are imposed on the process of speaking itself. Language materials confirm the purpose avoid of death nominations. The language units structural characteristics show that the death concept is mostly described by predicate or infinitive constructions, sometimes complicated by additional elements that give this image the processing sign. Frequently the keywords are replaced by the substitutes containing such mental images as land, world, soul / spirit, path / road etc. Decoding these paraphrase constructions requires contextual guidance and knowledge of Ukrainian cultural features.